Beyond the MBG Plate: The Influence of Food Preferences and Food Neophobia on Students’ Food Consumption Behavior - Desy Bariyyatul Qibtiyah; Moh. Fakhri Siddiqi; Ica Maulina Rifkiyatul Islami; Ari Okta Viyani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) is a national strategic policy in the food and nutrition sector aimed at improving the quality of human resources from school age. Based on studies from Bappenas, the presidential special envoy for Food Security, and several credible news sources, food waste in Indonesia remained substantial in 2025. Indonesia ranks 4th in food waste globally, resulting in national economic losses of up to IDR 500 trillion per year. Part of this food waste is contributed by the Free Nutritious Meal Program (MBG). Therefore, minimizing food waste in the MBG Program is important. One way to minimize MBG food waste is by understanding the preferences and consumption behavior patterns of students receiving MBG. To date, evaluation of the MBG program has been dominated by nutritional and food distribution approaches, while studies based on students' consumption behavior remain relatively limited. This condition indicates the urgency of research to produce scientific evidence supporting the strengthening of MBG policy based on food consumption behavior. This study aims to examine the effect of food preference on the consumption behavior of MBG recipient students, with food neophobia as a mediating variable. This study also aims to elaborate on other factors shaping the consumption behavior of MBG recipient students, as well as to develop a model of consumption behavior for MBG recipient students. The study employs a mixed-method approach. The quantitative approach was conducted through a questionnaire survey, with data analyzed using SEM-PLS. Meanwhile, the qualitative approach was conducted using the ZMET technique (interviews using images). The results show that food preference has a significant positive effect on consumption behavior, both directly and through the mediation of food neophobia, while food neophobia has a significant negative effect on consumption behavior. Qualitative findings through ZMET confirm that visual appeal and nutritional content are the main drivers of student preference, while poor food quality and safety are the main triggers of food neophobia and potential food waste.